Prediction of falling film evaporation on the AP1000 passive containment cooling system using ANSYS FLUENT code. (September 2016) - Wang, Xianmao; Chang, Huajian; Corradini, Michael; Cong, Tenglong; Wang, Jun
Highlights: The Eulerian Wall Film (EWF) model is tested and validated. Falling film evaporation is studied using EWF model. Thermal–hydraulic phenomena in the PCCS channels are analyzed. Abstract: AP1000 nuclear plant is an advanced pressurized reactor developed by Westinghouse Electric Company (WEC), with several passive systems applied to the plant to increase its safety. One of the main passive systems is the passive containment cooling system (PCCS), which aims to ensure the integrity of the containment and remove decay heat from the containment during postulated accidents. Film evaporation outside the steel vessel wall plays an important role for the heat removal process in the PCCS. In this study, the Eulerian Wall Film model in ANSYS FLUENT is applied to study falling film evaporation and natural convection outside the PCCS of AP1000. The thermal–hydraulic phenomena of both liquid film and gas mixture in the outside air flow path of the PCCS are analyzed. The Eulerian Wall Film model shows promising performance in modeling falling film behavior and mass transfer between liquid film and gas phase.